Association between cholesterol levels and dementia risk according to the presence of diabetes and statin use: a nationwide cohort study - You-Bin Lee; Min Young Kim; Kyungdo Han; Bongsung Kim; Jiyun Park; Gyuri Kim; Kyu Yeon Hur; Jae Hyeon Kim; Sang-Man Jin (Scientific Reports, 2022)
Abstract We explored the association between cholesterol levels and dementia risk according to the presence of diabetes and statin use. In this population-based longitudinal cohort study, the Korean National Health Insurance Service datasets (2002–2017) were used. Among individuals aged ≥ 40 years who underwent health examinations in 2009 (N = 6,883,494), the hazard of dementia was evaluated according to cholesterol levels. During a median 8.33 years, 263,185 dementia cases were detected. In statin non-users with or without diabetes, the hazards of all-cause dementia were highest for those in the lowest quartile or quintile of low-density lipoprotein-cholesterol (LDL-C) level, showing an inverted J-shaped relationship. Among statin users with or without diabetes, an advance in LDL-C group was associated with an increase in hazards of all-cause dementia. In statin users with diabetes, even very low LDL-C level was not associated with an increased risk of all-cause dementia. Although there was a seemingly paradoxical association between low LDL-C level and dementia risk in statin non-users, the trend was not observed in statin users and is not likely to be clinically relevant. Rather, an advance in LDL-C levels was associated with an increase in the hazard of all-cause dementia in statin users, regardless of the presence of diabetes.